Increasing excise taxes in the presence of an illegal cigarette market: the 2011 Brazil tobacco tax reform - Roberto Magno Iglesias
ABSTRACT The Brazilian cigarette excise tax reform of 2011 increased tax rates significantly in the presence of a high proportion of illegal and cheap cigarettes contributing to total consumption. Prior to 2011, tobacco tax policy in Brazil had reduced excise tax share on consumer prices, for fear of smuggling. This report examines two hypotheses explaining why tax authorities changed direction. The first is related to lack of concern regarding smuggling in tobacco industry pricing behavior before 2011 (rather than reducing prices following tax reduction, legal companies increased net of tax prices above inflation and key costs). The second hypothesis regards inconsistent industry assessments of the size of the illicit market, which ultimately undermined the credibility of the industry with tax authorities. The author concludes that the 2011 reform was designed to revert the weakness of previous policies, and did indeed succeed. The post-2011 experience in Brazil indicates that increased cigarette excise taxes can increase government revenues and reduce smoking prevalence and consumption despite widespread smuggling of tobacco products.